The overstory : a novel - Powers, Richard 1957-; Gene Berry and Jeffrey Campbell Collection (Library of Congress) (London : Penguin, 2018)
"The Overstory is a novel by Richard Powers published in 2018 by W. W. Norton & Company. It is Powers' twelfth novel. The book is about nine Americans whose unique life experiences with trees bring them together to address the destruction of forests. Powers was inspired to write the work while teaching at Stanford University, after he encountered giant redwood trees for the first time." -- Wikipedia